THE UTILIZATION OF ANDROID BASED DENTAL GUARD APPLICATION ON IMPROVING KNOWLEDGE OF DENTAL CARIES - Habib Imaduddin Fadhlurrahman; Sunomo Hadi; Imam Sawro Edi; Ratih Larasati; Anshad Ansari (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2024)
The case of dental and oral health commonly encountered in the community includes tooth decay (caries) and periodontal disease. Researchers have identified a high percentage of caries in children. The research aims to assess the impact of an Android-based application called Dental Guard on improving knowledge about tooth decay among 5th-grade students at SDN Ngagel 1 Surabaya. The study utilized a Pre-Experimental design with a One-Group Pretest-Posttest approach. Data were collected using questionnaires before and after the intervention. The analysis revealed an increase in knowledge about tooth decay among students in class 5B at SDN Ngagel 1 Surabaya after the Dental Guard intervention. Prior to using the Dental Guard app, students’ knowledge was categorized as “sufficient,” while after using the app, it improved to the “good” category.